Correction: Interfacial engineering between SnO2/MAPbI3 by maleate pheniramine halides toward carbon counter electrode-based perovskite solar cells with 16.21% efficiency. (23rd February 2023) - Cao, Duoling; Li, Zuhong; Li, Wenbo; Pei, Ke; Zhang, Xu; Wan, Li; Zhao, Li; Cherevan, Alexey; Eder, Dominik; Wang, Shimin
Abstract : Correction for 'Interfacial engineering between SnO2 /MAPbI3 by maleate pheniramine halides toward carbon counter electrode-based perovskite solar cells with 16.21% efficiency' by Duoling Cao et al., Mater. Chem. Front., 2023, ; https://doi.org/10.1039/d2qm01149b .